SIFAT PULP SODA ANTRAKINON KAYU AKASIA (ACACIA MANG/UM WILLD.) DAN AGATHIS (AGATHIS DAMMARA RICH) - Kayano Purba; Putritjatur Budilistyani; Surdiding Ruhendi; Rena M Siagian (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
The anthraquinone soda pulping trials have been conducted by using Acacia mangium Willd. and Agathis dammara Rich woods to investigate the effect of anthraquinone and its optimum usage on the pulp properties. The pulping trials have been conducted individually in a. rotary digester using soda process, with 16% of active alkali, wood to liquor ratio 1 : 4, maximum temperature 170°C and keeping the maximum temperature for two hours The anthraquinone catalyst was given in five levels, namely 0.00, 0.05, 0.10, 0.15 and 0.20% of the weight of oven dry basis wood.The result of the investigation showed that the variation in anthraquinone used had a significant effect on the pulp yield, tear strength, tear index, stretch and permanganate number of the pulp from Acacia mangium wood. By adding the same catalyst in the pulping trials of Agathis dammara wood it was found that such treatment had a significant effect on the pulp yield, tear strength, tear index, tensile strength, tensile index, breaking length, folding endurance, and bursting strength.It was found that the addition of anthraquinone catalyst tended to increase of the pulp yield of Acacia mangium and Agathis dammara, and to decrease the permanganate number of the pulp of Acacia mangium. In general, the addition of anthraquinone catalyst is increasing the physical properties of both wood species, but decreasing the bursting strength of the Agathis dammara putp.Compared to the classification of hardwoods. from tropical forest according to Misra, based on the pulp yield, alkali consumption, permanganate number, and stretch, the Acacia mangium pulp could be categorized as the first quality class, based on the breaking length as the second quality class, and based on the folding endurance it could be categorized as the third or fourth quality class. The optimum cooking condition of Acaciamangium was obtained by add- ing of 0.05% of anthraquinone catalyst. The optimum cooking condition of Agathis dammara was obtained with 0.10% anthraquinone catalyst. Based on the Indonesia Industrial Standard (Sll.08030-83), at this level. the resulting pulp can subsitute the unbleached sulphate pulp from conifer wood.